Collection of hybrid tea roses at M. M. Hryshko National Botanical Garden, NAS of Ukraine - С. В. Васьківська; В. І. Чижанькова (Plant Varieties Studying and Protection)
Purpose. To analyze thecollection of hybrid tea roses for the countries of origin, flower color, years of breeding. To select best modern cultivars for use in landscaping basing on evaluation of ornamental properties and economic characters.